All-day freshwater production enabled by an active continuous sorption-based atmospheric water harvesting system. (15th July 2022) - Wang, Wenwen; Yang, Tianyu; Pan, Quanwen; Dai, Yanjun; Wang, Ruzhu; Ge, Tianshu
Graphical abstract: Highlights: An all-day freshwater harvester is constructed and tested practically on an island. Continuous water harvester yields 0.67 gwater gsorbent -1 h −1 at 31 °C and 66–93% RH. Feasibility of air-cooled condensation for large-scale air water harvester. Matching of condensation and desorption is vital to practical water generation. Low grade heat source can be applied for regeneration, like solar energy. Abstract: Recent researches have demonstrated sorption-based atmospheric water harvesting (SAWH) as a sustainable, energy-efficient, and low-cost strategy to alleviate the water crisis. But the low daily water productivity of devices (L/kg day −1 ) remains a bottleneck to achieve efficient water production as they are merely allowed for intermittent operation. This limitation makes it rather challenging to deploy discontinuous SAWH systems for practical water production at large scales. Herein, we fabricated an active continuous SAWH (AC-SAWH) device with optimized sorbent bed structure. By configuring two sorbent beds and using nano-porous adsorbent by confining lithium chloride in silica sol modified activated carbon fiber felt (ASLI) as atmospheric water adsorbents, such a novel design enables water production in a continuous mode, delivering a water productivity of 8.3 kg day −1 or 0.67 kg h −1 at a regeneration temperature of 90 °C, with a thermal efficiency of 32.6%. This is the first exploration in continuous water production with a large-scale SAWH device, meeting personal drinking water demand of 5 L day −1 and demonstrating a promising water productivity for personal/household utilization in islands. With its excellent all-day freshwater harvesting performance and a scalable process, this continuous SAWH system is potential to make a contribution to the global water-energy-climate nexus.